The sensual image in the poetry of Ibn Mughbar al – Andalusi - عبد الرضا عبد الصاحب إسراء (Al-Adab Journal, 2018)
The research concluded that the poet Ibn Jubeir al-Andalusi is a poet who is distinguished by his poetic image which stems from the depth of his thinking influenced by the Andalusian environment as well as his broad culture and the depth of his great imagination. The poet invented various senses in the weaving of his poetry, And the poet mastered the use of sensory image to approximate what is just or moral as well as it has created a great creativity in the recruitment of the abstract to approximate what is significant and the latter a little Maabdoa by it because it needs a poetic energy that makes the senses imaginary and abstract. Color tone Wide in the sensual image